On-board health monitoring of power modules in inverters driving induction motors - Aliyu, Attahir Murtala (2017)
This thesis presents an on-board methodology for monitoring the health of power (converter) modules in drive systems. The ability to keep regular track of the actual degradation level of the modules enables the adoption of preventive maintenance, reducing or even eliminating altogether the appearance of failures during operation, significantly improving the availability of the power devices. The novelty of this work is twofold: the complete system that is used to achieve degradation monitoring; combining the heating technique (to obtain thermal transient) and the measurement without additional power components such as IGBT, MOSFETS, which affects the reliability, power density and complexity. The only additional component is an analog measurement circuit, which can be integrated into the gate drive board. The test routine is carried out during non-operational periods and idle times. Trains are used as a case study, where checks for degradation are made when the train is not in use, such as at the end of the day, after daily operation or at the start before daily operation and other non-operational periods. It is important to keep the train at standstill while tests are carried out. Hence a methodology to heat the devices with current from the input supply while keeping the motor load at a stand-still is presented. Experimental results obtained from this show that it is possible to implement an on-board health monitoring system in converters which measures the degradation on power modules. The work uses the concepts of vector control heating and structure function to check for degradation. It puts forward a system that is used on-board to measure the cooling curve and derive the structure function during idle times for maintenance purposes. The structure function is good tool for tracking the magnitude and location of degradation in power modules. Vector control gives the advantage of controlling the motor with field current and torque current (similar concept to DC motors).